1961
DOI: 10.1083/jcb.9.3.567
|View full text |Cite
|
Sign up to set email alerts
|

INTRACELLULAR LOCALIZATION OF KYNURENINE IN THE FATBODY OF DROSOPHILA

Abstract: A B S T R A C TLight blue fluorescent globules accumulate in the cells of the anterior region of the fatbody of Drosophila larvae near the time of pupation. This fluorescent material appears in the Ore-R wild type strain as well as m u t a n t strains in which the synthesis of both the red and brown eye pigments is affected. The vermilion mutant, which is characterized by the absence of the brown pigment component in the eye, was the only strain among those examined which did not develop the light blue fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1963
1963
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 6 publications
(2 reference statements)
2
17
0
Order By: Relevance
“…The light blue fluorescence characteristic of kynurenine is localized in globular cytoplasmic inclusions in the wild type Ore-R strain. These autofluorescent inclusions are restricted to the cells of the anterior region of the fatbody, and as described previously (21,22) there is a sharp autofluorescent boundary created by the intensity of the kynurenine autofluorescence in these cells in contrast to the autofluorescence of the adjacent cells involved in pteridine metabolism. Under the usual culture conditions no variation in the position of this boundary is noted, and the region of the fatbody containing kynurenine terminates in a row of ceils proceeding ventrocaudad and forming an arc of autofluorescent material when viewed from the lateral aspect.…”
Section: Distribution Of Kynurenine In Suppressor Mutantssupporting
confidence: 75%
See 1 more Smart Citation
“…The light blue fluorescence characteristic of kynurenine is localized in globular cytoplasmic inclusions in the wild type Ore-R strain. These autofluorescent inclusions are restricted to the cells of the anterior region of the fatbody, and as described previously (21,22) there is a sharp autofluorescent boundary created by the intensity of the kynurenine autofluorescence in these cells in contrast to the autofluorescence of the adjacent cells involved in pteridine metabolism. Under the usual culture conditions no variation in the position of this boundary is noted, and the region of the fatbody containing kynurenine terminates in a row of ceils proceeding ventrocaudad and forming an arc of autofluorescent material when viewed from the lateral aspect.…”
Section: Distribution Of Kynurenine In Suppressor Mutantssupporting
confidence: 75%
“…The methods used for collecting and raising Drosophila larvae for the present experiments as well as the preparations of cells for fluorcscencc microscopy were the same as those reported previously (21 the anterodorsal region of the fatbody served as the experimental material, and the dorsolateral and the caudal regions of the fatbody were selected as control tissues. Each of the pieces of fatbody was implanted into a 2-day-old vermilion adult male utilizing a micro injection apparatus (19).…”
Section: Site Of Synthesis Of Kynureninementioning
confidence: 99%
“…Since the active substance, v+ or kynurenine, could not be extracted from the fat body, it was concluded that the fat body is capable of kynurenine production. This conclusion was recently corroborated by a more direct approach (Rizki, 1961).…”
Section: Introductionsupporting
confidence: 54%
“…As however, the overexpression did not alter the trehalose levels ( Figure 5C). This is perhaps because dAkh expresshown in Figure 5F, AKH-CD fat bodies gave rise to background signals originating from endogenous ausion levels are not proportional to the amounts of AKH peptide released; thus, circulating AKH levels in UAStofluorogenic materials in this tissue (Rizki 1961). By comparison, immunofluorescent signals detected in dAkh/ϩ; dAkh-gal4/ϩ animals may approximate those in wild type.…”
Section: Targeted Ablation Of Akhergic Neuronsmentioning
confidence: 98%